Inter-American yearbook on human rights / Anuario Interamericano de derechos humanos (2018). Vol. 34 (Vol. 2) - Inter-American Commission on Human Rights (Leiden : Koninklijke Brill NV, 2019)
The 2018 'Inter-American Yearbook on Human Rights' provides an extract of the principal jurisprudence of the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights. Part One contains the Decisions on the Merits of the Commission, and Part Two the Judgments and Decisions of the Court.0The Yearbook is partly published as an English-Spanish bilingual edition. Some parts are in English or Spanish only.
Keywords: Civil rights -- Periodicals -- America; Civil rights -- Periodicals -- South America; Yearbooks